A multi-scale model for studying failure mechanisms of composite wind turbine blades. (15th March 2019) - Ye, Junjie; Chu, Chenchen; Cai, Heng; Hou, Xiaonan; Shi, Baoquan; Tian, Shaohua; Chen, Xuefeng; Ye, Jianqiao
Abstract: Composite structures have been widely used in wind turbine equipment for their high stiffness to mass ratio and high strength. A major concern in the use of composite materials is their susceptibility to various micro damage, such as fiber breakage and matrix crack, which will lead to macroscopic structural fracture. In this paper, a multi-scale modeling strategy is proposed to investigate failure mechanisms and damage evolution of composite blades with initial defects from microscopic damage (including fiber fractures and matrix cracks) to macroscopic fracture. At the microscopic scale, an isoparametric micromechanical model is developed to calculate microscopic stresses and simulate microscopic damage. At the laminar scale, the classic laminate theory is employed to evaluate the laminate stiffness. At the structural scale, a reverse modeling technology is proposed to accurately acquire structural dimensions of a wind turbine blade, and a macroscopic 3D model is implemented into ANSYS/LS-DYNA software. By comparing with the experimental data, it is demonstrated that the proposed multi-scale method is suitable to predict mechanical properties of complex composite structures effectively.